Studi Kesiapan Guru Dalam Mengintegrasikan Peran Teknologi Digital pada Pembelajaran Kurikulum Merdeka di Sekolah Dasar - Afnani, Muhammad Rozikul; Attalina, Syailin Nichla Choirin (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study aims to determine the readiness of teachers in integrating the role of digital technology in Independent Curriculum learning at SDN 2 Bringin. This study examines the factors that influence the readiness and obstacles of teachers in integrating educational technology in Independent Curriculum learning at SDN 2 Bringin. With technology, teachers can present a more interesting and interactive learning atmosphere. Independent Curriculum is a curriculum designed to strengthen several student abilities, one of which is digital literacy.Method – This research is qualitative research. Data collection in this study uses observation, interview, and documentation techniques. Data analysis uses data collection, data reduction, data presentation, and drawing conclusions. Findings – The results of the study showed that teacher readiness in integrating digital technology in learning is very important. Teachers must have good competence; in addition, skills in utilizing digital technology are an important point in measuring teacher readiness in implementing digital-based learning. The results of the study also found that most teachers at SDN 2 Bringin already have basic skills related to digital technology, but they still need to be improved. In addition, facilities and infrastructure that are less supportive are also obstacles for teachers at SDN 2 Bringin to integrate digital technology in learning. Research Implications – This research is expected to encourage motivation for teachers to improve their understanding and skills regarding digital technology that can be utilized in learning. The findings of this study highlight the ability of teachers to utilize digital technology in learning. Developing teacher quality through training is one of the efforts to improve the quality of learning in the digital era. Given the limitations of the information used, further research with a larger sample is highly recommended to produce better findings.